Dexmedetomidine Alleviates LPS-Induced Neuronal Dysfunction by Modulating the AKT/GSK-3β/CRMP-2 Pathway in Hippocampal Neurons - Zeng W (Dove Medical Press, 2021)
Wei Zeng,1,2 Chunyuan Zhang,2 Qingshan Long,3 Yalan Li1 1Department of Anesthesiology, The First Affiliated Hospital of Jinan University, Guangzhou, 510630, Guangdong, People’s Republic of China; 2Department of Anesthesiology, Affiliated Boai Hospital of Zhongshan, Southern Medical University, Zhongshan, 528400, Guangdong, People’s Republic of China; 3Department of Neurosurgery, Huizhou Third People’s Hospital, Guangzhou Medical University, Huizhou, 516002, Guangdong, People’s Republic of ChinaCorrespondence: Yalan LiDepartment of Anesthesiology, The First Affiliated Hospital of Jinan University, Guangzhou, 510630, Guangdong, People’s Republic of ChinaEmail tyalan@jnu.edu.cnObjective: Dexmedetomidine, an α 2-adrenergic receptor agonist, mitigates cognitive dysfunction in elderly patients after surgery with general anesthesia. However, the underlying mechanism by which dexmedetomidine reduces cognitive dysfunction remains to be fully elucidated. The aim of this study was to investigate the effects of dexmedetomidine on lipopolysaccharide (LPS)-induced neuronal dysfunction in cultured hippocampal neurons.Methods: LPS, in the presence and absence of dexmedetomidine, was applied to cultured hippocampal neurons to mimic post-surgical inflammation. Neuronal morphology, including neurite outgrowth and synaptic transmission, was observed, and miniature excitatory postsynaptic currents were recorded by electrophysiological patch-clamp.Results: LPS significantly impaired neurite outgrowth in hippocampal neurons in a concentration- and time-dependent manner, which was reversed by dexmedetomidine treatment. Electrophysiological patch-clamp results showed that LPS induced synaptic transmission dysfunction, which was restored after dexmedetomidine addition. Furthermore, Western blotting assays showed that LPS suppressed the AKT/GSK-3β/CRMP-2 signaling pathway and dexmedetomidine countered the inhibitory effect of LPS by re-activating this pathway.Conclusion: In general, dexmedetomidine protected against the effects of LPS-induced hippocampal neuron damage, including neurite outgrowth and synaptic transmission. Overall, dexmedetomidine modulated the AKT/GSK-3β/CRMP-2 signaling pathway to alleviate LPS-induced neurological dysfunction.Keywords: dexmedetomidine, postoperative cognitive dysfunction, neurological impairment, AKT, GSK-3β, CRMP-2